Biodiversity of UV-Resistant Bacteria in Antarctic Aquatic Environments - Coppola, Daniela; Lauritano, Chiara; Zazo, Gianluca; Nuzzo, Genoveffa; Fontana, Angelo; Ianora, Adrianna; Costantini, Maria; Verde, Cinzia; Giordano, Daniela (Journal of Marine Science and Engineering, 2023)
Antarctica is an untapped reservoir of bacterial communities, which are able to adapt to a huge variety of strategies to cope with extreme conditions and, therefore, are capable of producing potentially valuable compounds for biotechnological applications. In this study, 31 UV-resistant bacteria collected from different Antarctic aquatic environments (surface sea waters/ice and shallow lake sediments) were isolated by UV-C assay and subsequently identified. A phylogenetic analysis based on 16S rRNA gene sequence similarities showed that the isolates were affiliated with Proteobacteria, Actinobacteria and Firmicutes phyla, and they were clustered into 15 bacterial genera, 5 of which were Gram negative (Brevundimonas, Qipengyuania, Sphingorhabdus, Sphingobium, and Psychrobacter) and 10 of which were Gram positive (Staphylococcus, Bacillus, Mesobacillus, Kocuria, Gordonia, Rhodococcus, Micrococcus, Arthrobacter, Agrococcus, and Salinibacterium). Strains belonging to Proteobacteria and Actinobacteria phyla were the most abundant species in all environments. The genus Psychrobacter was dominant in all collection sites, whereas bacteria belonging to Actinobacteria appeared to be the most diverse and rich in terms of species among the investigated sites. Many of these isolates (20 of 31 isolates) were pigmented. Bacterial pigments, which are generally carotenoid-type compounds, are often involved in the protection of cells against the negative effects of UV radiation. For this reason, these pigments may help bacteria to successfully tolerate Antarctic extreme conditions of low temperature and harmful levels of UV radiation.